Millennial votes in the 2019 Philippine National Election: A quantitative approach - Emilio N. Timoteo Jr. (Applied Quantitative Analysis, 2022)
This study aimed to know factors influencing the voting preferences of the Millennial generations during the 2019 Philippine National Election. According to the official social media of the Commission on Elections (COMELEC), more than 61.8 million voters for the election belonged to the Millennial generation. Using a questionnaire survey, this study measured and correlated the respondents' profile, Candidate's Attribute, Endorsement Method, Platform and Campaign Strategy, and top ten characteristics of the candidates. These variables were all surveyed, tallied, and analyzed. The survey involved 138 college students who participated in the Voter’s Education Program led by COMELEC Taguig. This study reveals that the top three characteristics that the respondents wanted to see in a candidate are: not corrupt, wise, and a Godly person. In the future, this study can be replicated in a larger population of Millennials. It can be a great avenue of change in the political atmosphere of the Philippines. Finally, this study could bring new inspirations to those aspiring to run for public offices.